The Current State of Comfort with Interpersonal Touch Among University Students - Tuong, Nguyen Van; Duong, Huynh Phu (English Department, Faculty of Humanities, Andalas University, 2025)
This study surveyed 1,379 undergraduate students at the University of Social Sciences and Humanities, Vietnam National University, Ho Chi Minh City, to explore their level of comfort with interpersonal touch—a prominent social behavior among Gen Z youth. Data were collected online between November and December 2024 and analyzed using SPSS 26.0. Results showed that students’ comfort with interpersonal touch was relatively low. No significant differences were found by academic year or part-time work status. However, significant differences emerged in relation to gender, sexual orientation, and academic performance.